2019
DOI: 10.1186/s12954-019-0343-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for people who use anabolic androgenic steroids: a scoping review

Abstract: Background: A growing body of evidence suggests that anabolic androgenic steroids (AAS) are used globally by a diverse population with varying motivations. Evidence has increased greatly in recent years to support understanding of this form of substance use and the associated health harms, but there remains little evidence regarding interventions to support cessation and treat the consequences of use. In this scoping review, we identify and describe what is known about interventions that aim to support and ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 191 publications
1
36
0
Order By: Relevance
“…The priorities identified provide clear objectives for behavior change interventions targeting people who use AAS from the perspectives of those who work with them, and highlight that current UK public health approaches are only tackling some of what stakeholders in this study perceive to be important policy goals. The increasing evidence base on physical and mental health harms associated with AAS use (Pope et al, 2014) and examples of treatments given in response to these (Bates et al, 2019) supports the needs identified here to not only tackle the risk of BBVs, but to reduce risks of poor health outcomes associated with long term use. The findings suggest that health professionals and other stakeholders who work with people who use AAS believe that an expanded approach is required that is designed in response to the needs of this population; one that includes interventions to support them to manage their risk through moderation and support their health following cessation, as well as interventions to motivate cessation and prevent initiation.…”
Section: Discussionsupporting
confidence: 62%
“…The priorities identified provide clear objectives for behavior change interventions targeting people who use AAS from the perspectives of those who work with them, and highlight that current UK public health approaches are only tackling some of what stakeholders in this study perceive to be important policy goals. The increasing evidence base on physical and mental health harms associated with AAS use (Pope et al, 2014) and examples of treatments given in response to these (Bates et al, 2019) supports the needs identified here to not only tackle the risk of BBVs, but to reduce risks of poor health outcomes associated with long term use. The findings suggest that health professionals and other stakeholders who work with people who use AAS believe that an expanded approach is required that is designed in response to the needs of this population; one that includes interventions to support them to manage their risk through moderation and support their health following cessation, as well as interventions to motivate cessation and prevent initiation.…”
Section: Discussionsupporting
confidence: 62%
“…The scientific community should intensify its efforts to assess the pathophysiology of behavior and cognitive impairment due to long term AAS exposure. Moreover, evidence is urgently required to support the development of a reliable diagnostic tool to identify precociously AAS abuse as well as evidence-based therapy [ 57 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…The links between AAS use and mental health identified here highlights the importance of people who use AAS having access to health services to obtain treatment. It is, however, well-established that access to health services for this sub-population is generally limited; not only due to the lack of treatment available ( 73 ) but also due to a lack of knowledge amongst health professionals about these substances ( 74 , 75 ). This lack of access has been exacerbated due to the COVID-19 pandemic with health services, including alcohol and other drugs services, needing to close down or restricting their access ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%